SULPHATE SOURCES IN THE SAVA AND LJUBLJANICA RIVERS, SLOVENIA, INFERRED FROM SULPHUR AND OXYGEN ISOTOPE COMPOSITIONS - Vokal-Nemec B.; Szaran Ja.; Trembaczowski A.; Halas S.; Dolenec T.; Lojen S. (My University, 2006)
Measurements were made of sulphur and oxygen isotope ratios of sulphate in some Slovenian rivers, lakes and tap waters. δ34S ranged from −0.2 to + 13.3‰, δ18O ranged from +4.9 to + 13.6‰, and the sulphate content varied from 0.8 to 41.4 mg/L. Rivers flowing from the Julian Alps contain a very low amount of sulphate that is leached from a thin horizon of soil by rain. As confirmed by their low δ18O values, these sulphates do not enter the rivers directly in rain, but arise from biochemical cycling in the soil. The low δ34S of this sulphate indicates that it originates from the oxidation of sedimentary sulphides. The evolution of sulphates along the river course was investigated for the Sava and Ljubljanica rivers. The variations observed in sulphate from the waters studied result from variations in the contribution of sulphates of different origin. Downstream the Sava River sulphate is depleted in the heavy isotopes of both sulphur and oxygen, with δ-values gradually tending toward the δ-values of groundwater sulphates in the watershed. In contrast, the δ-values of sulphate in the Ljubljanica River are almost constant and similar to those of sulphate in local groundwater. Introduction of water from Italian and Slovenian mines was recorded in the Soča River, where the lowest δ34S value of sulphate sulphur (−0.2‰) was observed. In addition, the influence of sulphate from the oxidation of sedimentary sulphides was recorded in the Sotla River. No evidence was found for introduction of sulphate from factories.
Keywords: LJUBLJANICA RIVER; OXYGEN ISOTOPES; SAVA RIVER; SULPHATES; SULPHUR ISOTOPES